2021
DOI: 10.1063/5.0064193
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of particles effects on wall-normal velocity fluctuations in sand-laden atmospheric surface layer flows

Abstract: Based on the high-quality observational data in the Qingtu Lake Observation Array (QLOA), the difference in the energy distribution, the scale of the coherent structures, and the amplitude modulation effect of the wall-normal velocity fluctuations between particle-free and particle-laden flow in the atmospheric surface layer are analyzed. The results show that the presence of particles enhanced the wall-normal turbulence intensity, especially the increase at the top of the logarithmic region is more significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…Substantial modification of VLSMs (and turbulence statistics more generally) was observed in the present study, and evidence of similar behaviour is being observed in the atmospheric surface layer (Liu et al. 2021). The complexity of the nonlinear coupling of inertial particles with high- wall turbulence and the high cost of the simulations, however, precludes a full description at this stage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Substantial modification of VLSMs (and turbulence statistics more generally) was observed in the present study, and evidence of similar behaviour is being observed in the atmospheric surface layer (Liu et al. 2021). The complexity of the nonlinear coupling of inertial particles with high- wall turbulence and the high cost of the simulations, however, precludes a full description at this stage.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we recall the scientific questions posed at the beginning of this paper, namely whether the turbulence modification of VLSMs will persist at high Reynolds number, and whether the mechanisms which modify them are similar to those found in . Substantial modification of VLSMs (and turbulence statistics more generally) was observed in the present study, and evidence of similar behaviour is being observed in the atmospheric surface layer (Liu et al 2021). The complexity of the nonlinear coupling of inertial particles with high-Re wall turbulence and the high cost of the simulations, however, precludes a full description at this stage.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, sandstorms contain not only suspended particles scattered in the air, but also saltating particles at near-wall locations (<0.5 m) (Shao 2008;Zheng 2009). The experimental set-up was improved in 2021 based on the deployment in 2016 to collect information of near-wall saltating particles in wind-blown sand flows/sandstorms Liu, He & Zheng 2021). In addition to the equipment in 2016, an additional pair of sonic anemometer and aerosol monitor were placed at 0.5 m. For the particle concentration measurements of near-wall saltating particles, five sand particle counters (SPC-91, Niigata Electric Co., Ltd.; f s = 1 Hz; z = 0.03, 0.05, 0.1, 0.28 and 0.5 m) and five outdoor hot wires (ComfortSence 54T35, Dantec Dynamics A/S; f s = 2 Hz; z = 0.03, 0.05, 0.1, 0.16 and 0.28 m) were deployed in the range of 0.03-0.5 m (shown in figure 1d,e).…”
Section: Experimental Site and Set-upmentioning
confidence: 99%
“…2017), and the turbulence statistics in particle-laden flows in QLOA have been analysed in detail in Liu et al. (2021, 2023).…”
Section: Experiments and Datamentioning
confidence: 99%